Estudio de prefactibilidad para la instalación de una planta de producción de juegos de platos, vasos y cubiertos biodegradables - Jimenez Maldonado, Micaela Gloria (2021)
The present research work seeks to determine the feasibility of installing a production plant to manufacture biodegradable dishes, cups, and cutlery based on organic waste to sell nationwide. The first chapter will address its objectives which will determine the economic, technical, financial, and social viability. In addition, it will address the context in which the product will be offered. The second chapter will present the referential framework which encompass previous research works related to this one. Furthermore, the conceptual framework will develop the essential concepts to know to understand this research work. The third chapter will develop the methodology this work follows; next, a market study will be carried out which will use a survey to the target audience; following, this chapter will determine the localization and the plan layout, which will rule the district where the plan will be located and the space necessary for it. Also, it will describe the production process and the organization of human resources through the plant and the administrative facility. To end the third chapter, it will detail the investment necessary to start up the plan, an income, and expenses projections, which will be used to calculate the economic and financial evaluation, to determine the profitability of this project. Finally, the chapter ends by working out the social impact of the project in the stakeholders, calculating the social indicators. Finally, the fourth chapter will present the conclusions and recommendations.